The concept of experiential education and the interdisciplinary opportunities offered by physical activities. - Pastor Pradillo, José Luis (Pulso. Revista de educación, 2002)
The term "psychomotricity" has been subject to various interpretations, each based on different paradigms that reflect two distinct understandings of the development of its interventions. Furthermore, the selection of this approach influences the identification of objectives, the methods of execution, the teaching tools in the learning environment, and most importantly, the educator's presence. Experiential education, drawing on its own doctrinal and didactic parameters and principles, offers interdisciplinary possibilities that prove highly effective in achieving specific objectives, particularly at levels where a holistic approach is most critical.